2011
DOI: 10.3347/kjp.2011.49.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilusContributes to a Healthy Environment for Vaginal Epithelial Cells

Abstract: Lactobacillus species in the female genital tract are thought to act as a barrier to infection. Several studies have demonstrated that lactobacilli can adhere to vaginal epithelial cells. However, little is known about how the adherence of lactobacilli to vaginal epithelial cells affects the acidity, cell viability, or proliferation of the lactobacilli themselves or those of vaginal epithelial cells. Lactobacillus acidophilus was co-cultured with immortalized human vaginal epithelial cells (MS74 cell line), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…In fact, our findings hint that L. acidophilus is possibly associated with the abundance of specific bacterial species. This finding agrees with studies that have shown that L. acidophilus occurrence associates with a healthy cervix and a protective immune response, which may indicate its ability to enhance beneficial Lactobacillus species such as L. crispatus 41 44 . Alternatively, L. acidophilus occurrence may also lead to a decrease in the abundance of Lactobacillus species that generally dominate the CVM, facilitating the colonization by other microbes, an increase in diversity, and the transition to a different CST.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, our findings hint that L. acidophilus is possibly associated with the abundance of specific bacterial species. This finding agrees with studies that have shown that L. acidophilus occurrence associates with a healthy cervix and a protective immune response, which may indicate its ability to enhance beneficial Lactobacillus species such as L. crispatus 41 44 . Alternatively, L. acidophilus occurrence may also lead to a decrease in the abundance of Lactobacillus species that generally dominate the CVM, facilitating the colonization by other microbes, an increase in diversity, and the transition to a different CST.…”
Section: Discussionsupporting
confidence: 92%
“…However, only the gastric-isolated L. rhamnosus was able to produce an effect on cell proliferation through the sufficient reduction of the pH of the cell medium. By contrast, despite the fact that L. acidophilus reduces the cell medium to a pH of 4.5, this bacterial species has been reported to increase the proliferation of human vaginal epithelial cells [14]. Lactic has been shown to cause cell cycle arrest and apoptosis in human keratinocyte cells [15].…”
Section: Discussionmentioning
confidence: 97%
“…Interaction with mucin allows the lactobacilli to remain within the mucus layers, thereby contributing to the formation of multi-species biofilms (Wickstrom et al, 2013), which are essential for protection against intruding pathogens (Pi et al, 2011). Amongst the tested Lactobacillus species, L. fermentum ATCC 23271 was the only to produce moderate biofilm on plastic surface in comparison with other lactobacilli.…”
Section: Discussionmentioning
confidence: 99%